Group lending and endogenous social sanctions - Jean-Marie Baland; Rohini Somanathan; Zaki Wahhaj (University of Kent, School of Economics, 2014)
In recent years, microfinance institutions have expanded into group lending with individual liability, leaving out the joint liability clause which was an important feature in earlier lending contracts. Recent experimental evidence indicates that group lending may yield benefits, specifically lowering default rates, even in the absence of joint liability. In this paper, we develop a theoretical model where the public nature of group meetings means that borrowers have incentives to repay a group loan to safeguard their reputation. We show that the introduction of group loans with individual liability will cause sorting between joint liability and individual liability group loans. Specifically, borrowers who attach more importance to their reputation will select into individual liability loans, causing default rates and interest rates to rise for joint liability loans. The introduction of group loans with individual liability can even make joint liability loans infeasible in equilibrium.
Keywords: G21; O12; O16; D8; 330; Microfinance; Group Lending; Joint Liability; Social Sanctions; Reputation